Enhanced detoxification via Cyt-P450 governs cross-tolerance to ALS-inhibiting herbicides in weed species of Centaurea. (1st April 2023) - Palma-Bautista, Candelario; Vázquez-García, José G.; de Portugal, Joao; Bastida, Fernando; Alcántara-de la Cruz, Ricardo; Osuna-Ruiz, Maria D.; Torra, Joel; De Prado, Rafael
Abstract: Centaurea is a genus of winter weeds with a similar life cycle and competitive traits, which occurs in small-grains production fields in the central-southern of the Iberian Peninsula. However, most of herbicides recommended for weed management in wheat show poor control of Centaurea species. This study summarizes the biology, herbicide tolerance to acetolactate synthase (ALS) inhibitors, and recommended chemical alternatives for the control of Centaurea species. Four species ( C. cyanus L., C. diluta Aiton, C. melitensis L. and C. pullata L. subsp. baetica Talavera), taxonomically characterized, were found as the main important broadleaf weeds in small-grains production fields of the Iberian Peninsula. These species showed innate tolerance to tribenuron-methyl (TM), showing LD50 values (mortality of 50% of a population) higher than the field dose of TM (20 g ai ha −1 ). The order of tolerance was C. diluta (LD50  = 702 g ha −1 ) ≫ C. pullata (LD50  = 180 g ha −1 ) ≫ C. cyanus (LD50  = 65 g ha −1 ) >  C. melitensis (LD50  = 32 g ha −1 ). Centaurea cyanus and C. melitensis presented higher foliar retention (150–180 μL herbicide solution), absorption (14–28%) and subsequent translocation (7–12%) of TM with respect to the other two species. Centaurea spp. plants were able to metabolize 14 C-TM into non-toxic forms (hydroxylated OH-metsulfuron-methyl and conjugated-metsulfuron-methyl), with cytochrome P450 (Cyt-P450) monooxygenases being responsible for herbicide detoxification. Centaurea cyanus and C. mellitensis metabolized up to 25% of TM, while C. diluta and C. pullata metabolized more than 50% of the herbicide. Centaurea species showed 80–100% survival when treated with of florasulam, imazamox and/or metsulfuron-methyl, i.e., these weeds present cross-tolerance to ALS inhibitors. In contrast, auxin mimics herbicides (2, 4-D, clopyralid, dicamba, fluroxypir and MCPA) efficiently controlled the four Centaurea species. In addition, the mixture of ALS-inhibitors and auxin mimics also proved to be an interesting alternative for the control of Centaurea . These results show that plants of the genus Centaurea found in the winter cereal fields of the Iberian Peninsula have an innate tolerance to TM and cross-resistance to other ALS-inhibiting herbicides, governed by reduced absorption and translocation, but mainly by the metabolization of the herbicide via Cyt-P450. Graphical abstract: Image 1 Highlights: Four Centaurea sp. shown low susceptibility to tribenuron-methyl (TM). CYP450 inhibitors antagonize tolerance to TM. GST inhibitor do not antagonize the tolerance to TM. Absorption and translocation differences were found in the four Centaurea. Auxin mimics, alone or in mixture with other herbicides can be alternatives.